The Development of Correlation Model between Economic Development and Environmental Performance on the Basis of Non-Financial Reporting - Bogdanov, Vladimir Dmitrievich; Ilysheva, Nina Nikolaevna; Baldesku, Elena Valentinovna; Zakirov, Ulugbek Shakirovich (Economy of Regions, 2016)
The most common international standards for the non-financial reporting are reviewed. The Global Reporting Initiative (GRI) is determined as an optimal standard of sustainability reportingfor the use in the Russian conditions. The environmental component of guidance on the compilation of G4 non-financial reporting of GRI standard is analyzed, the contribution of each aspect in terms of the overall picture of sustainability is determined. The progress of economic science has outlined the importance of incorporating natural components. Moreover, the value of biological resources would be increased through time, and therefore, the economic development of the company cannot be in isolation. To determine the degree of harmony between the economic development and ecological condition of the territory where the company carries out the economic activities, the application of new approaches and methods is necessary. Based on the statistical methods, a correlation model between economic development and environmental performance is developed to identify their relationship on the basis of non-financial reporting. The developed model of correlation can be used by a wide range of oil and gas companies and its general principles by the companies of different industries. The results may be of interest to stakeholders, also, it can be used for administrative purposes, to serve as a platform for forecasting and adoption of administrative decisions to achieve harmony between economic development and environmental performance. The model of correlation has been tested for the data of non-financial reporting of the Russian largest oil and gas company JSC “Surgutneftegas”. The testing has shown a positive relationship between the two systems of the company’s sustainable development: economy and ecology. This obtained result demonstrates a high level of social responsibility of the company in terms of environmental protection. A further study in this field can produce more profound results that would help to achieve a wide sustainable development.